2015
DOI: 10.18632/oncotarget.3663
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic acid suppresses the development of pancreatic cancer by inhibiting pathways driving lipogenesis

Abstract: Ginkgolic acid (GA) is a botanical drug extracted from the seed coat of Ginkgo biloba L. with a wide range of bioactive properties, including anti-tumor effect. However, whether GA has antitumor effect on pancreatic cancer cells and the underlying mechanisms have yet to be investigated. In this study, we show that GA suppressed the viability of cancer cells but has little toxicity on normal cells, e.g, HUVEC cells. Furthermore, treatment of GA resulted in impaired colony formation, migration, and invasion abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…Collectively, the results of the present study indicated that GA suppressed the development of RCC. These results were consistent with previous studies demonstrating that GA plays an inhibitory biological role in cancer (12)(13)(14)(15)25). However, the biological effect of GA on RCC was observed at high concentrations of GA in vitro and it is uncertain whether this concentration would be possible in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Collectively, the results of the present study indicated that GA suppressed the development of RCC. These results were consistent with previous studies demonstrating that GA plays an inhibitory biological role in cancer (12)(13)(14)(15)25). However, the biological effect of GA on RCC was observed at high concentrations of GA in vitro and it is uncertain whether this concentration would be possible in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Fetal-derived Normal Human Astrocytes (NHA, Lonza) were maintained in Astrocyte Growth Medium (AGM, Lonza) supplemented with 0.3% FBS, 30 µl/mL ascorbic acid, 1 µl/mL rhEGF, 30 µg/mL gentamicin, 15 μg/mL amphotericin B, 2.5 µl/mL insulin, and 10 µl/mL L-glutamine. Early passages (1)(2)(3)(4) were used in these experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, our results demonstrated that resveratrol could activate AMPK (Thr172) and suppress the proliferation of pancreatic cancer cells, indicating the anti-proliferative action of AMPK in pancreatic cancer cells. The effect of AMPK on cell proliferation appears to be mediated through multiple mechanisms, mainly the regulation of cell cycle progression, inhibition of protein synthesis, and de novo fatty acid biosynthesis [40,41]. Previous reports have suggested that AMPK activation stabilizes and increases AMOTL1 steady-state protein levels, contributing to YAP inhibition [42].…”
Section: Discussionmentioning
confidence: 99%